Hubungan Indeks Massa Tubuh Dan Panjang Tungkai Dengan Kelincahan Pada Pemain Sepak Bola Di Salatiga Training Center Dan Puslat Salatiga Fc Kota Salatiga - Putri, Ditha Eka, Wijianto, SST.FT, M.OR (2016)
Background: Agility is the ability of the body to change direction with the speed at the time of the move without losing balance on the position of her body. Body composition is very influential towards the motion of a person. Agility plays a role that is especially against physical mobility, agility is not a single physical component, but is composed of component coordination, strength, flexibility, reaction time and power. Some of the factors that influence the agility description, the other Anthropometry, body type, age, gender, and weight. The purpose of the research: to find out whether there is a relationship between body time index with agility in salatiga training center and puslat salatiga fc in Salatiga. Find out if there is a relationship between the length of limbs with agility in salatiga training center and puslat salatiga fc in Salatiga city Research methods: method or the type of research used in this research is korelasional. Korelasional research is research that aims to find or no relationship and if there is, how closely the relationship as well as mean or whether that relationship. This research using survey method with engineering test and measurement. Technique of data analysis in this study is the analysis of regression to find whether there is a relationship between variables and the variables are bound. The analysis about the relationship between one variable is bound and three free variables. Research results: there is no relationship between the IMT with agility in salatiga training center with a value of r = 0113 with significant value-0302 > 0.05. and there is a relationship between the length of limbs with agility with a value of r = 753-significant value 0000 < 0.05. then there is no relationship between the IMT with agility in salatiga fc puslat with a value of r = 0822-with significant value 0000 < 0.05. While there is a relationship between the length of limbs with agility with a value of r = 0822-with ignificant value 0000 < 0.05 onclusion: there is no relationship between body mass index (IMT) with agility and there is a relationship between the length of limbs with agility training center in salatiga city of salatiga. No there is no relationship between body mass index (IMT) with agility and there is a relationship between the length of limbs with agility in salatiga puslat fc.